Legal Protection for Child Labor of Underage Newspaper Sellers in the Labor Law - Rajasa, Dimas Farazh; Hasyim, Yonani; Raspita, Desni (Universitas Muhammadiyah Palembang, 2023)
Everyone has the right to receive protection according to law, including children, the participation of parents is very important to protect their children by not committing violence, exploitation or employing them. The problem raised in this paper is children who are employed. because they are still underage, there are no regulations for child labor in Indonesia that clearly regulate the rules given. As regulated in the 1945 Constitution, Law no. 13 of 2003 concerning Manpower, ILO Convention, Law no. 35 of 2014 concerning Child Protection, in this writing the legal research used is normative in nature. Labor and child labor arrangements are regulated in several laws and government regulations. The regulations in force in Indonesia do not clearly stipulate the age limit and the type of work performed by child workers. In fact, the majority of children's involvement in work is driven by poverty or economic factors. Protection for children as workers has basically been regulated in several formulations of international laws and conventions that have been ratified by Indonesia. Currently, Indonesia has a policy on the protection of child labor and their rights. Various efforts have been made to overcome the problem of child labour, but in general the government's efforts have not run optimally. The implementation of laws and regulations has not matched expectations and reality. Efforts that can be made at this time are that the government in good faith monitors children who are working in each company so that by carrying out this monitoring the fulfillment of children's rights can be realized properly.